An exploratory investigation into strategic resilience in the US wine industry. (2nd January 2020) - Gilinsky, Armand; Ford, Judith; Newton, Sandra K.; Brown, Deanna
ABSTRACT: More frequent and destructive natural disasters have thrust the topic of strategic resilience to the forefront of managerial conversations around the globe. Stakeholders increasingly expect firms to have plans in place to mitigate these disasters and sustain, or quickly resume, their operations. The communities within which firms operate increasingly expect them to responsibly engage to sustain local economic and environmental assets. The climate and geography endemic to many wine grape-growing regions are also often vulnerable to wildfire, flooding and earthquakes. Via grounded field research, involving four case studies of wine businesses, we assessed perceived strategic resilience in the key wine regions of Napa and Sonoma Counties recently impacted natural disaster by applying content analysis to eight qualitative interviews from personnel at four bonded wineries. Our analysis found four conceptual constructs of organizational resilience: realizing a need, building stakeholder support, securing resources and capabilities and exemplifying best practices. These conceptual constructs could provide a roadmap for firms looking to increase their resilience in planning for natural disaster.